Development of Assessment Instruments for Disaster Resilient Campus Capacity - Hery Sumasto; Sulikah Sulikah; Nurwening Tyas Wisnu (Health Notions, 2019)
Indonesia is a country that has many natural disasters, because the archipelago, many volcanoes and the sea. The number of deaths that occur can be caused by a lack of knowledge, community skills when facing disasters. When a disaster strikes, people become very panicked and chaos can trigger many victims. Therefore it is necessary to have the right strategy in the form of disaster mitigation. This study aims to develop instruments to assess campus capacity in the face of disasters. The instrument in this study was the development of a SMAB (Madrasah Schools Safe from Disasters) instrument developed by National Disaster Management Agency. The steps in developing this instrument were: 1) initial study; 2) determine sub indicators; 3) compiling the instrument item grid; 4) compile instrument items; 5) testing instruments, 6) carrying out analysis; 7) revision of the instrument; 8) formulate the final instrument from the results of the study. There were 4 strong campus capacities, namely building structure; knowledge, attitude, and action; campus policy; and preparedness. After testing the validity, there were 28 invalid items from 48 items. All reliability test items that were valid items were reliable. This means that it can be used to measure strong campus capacity Keywords: capacity instruments; disaster mitigation; disaster resilient campus